We all want to change the world : my journey through social justice movements from the 1960s to today - Abdul-Jabbar, Kareem, 1947-; Obstfeld, Raymond, 1952- (Crown, 2025)
"For many, it can feel like change takes too long, and it might seem that we have not moved very far. But political activist Kareem Abdul-Jabbar believes that public protest is a vital part of affecting change, even if that change doesn't come "right now." In We All Want to Change the World, he examines the activism of people of all ages, ethnicities, and socio-economic backgrounds that helped change America, documenting events from the Free Speech Movement through the movement for civil rights, the fight for women's and LGBTQ rights, and, of course, the protests against the Vietnam War. At a time in our history when we are witnessing protests across campuses, within the labor movement, and following the killing of George Floyd, Abdul-Jabbar reminds us that protests are a lifeblood of our history: "Protest movements, even peaceful ones, are never popular at first... But there is a reason protest gatherings have been so frequent throughout history: They are effective. The United States exists because of them." Part history lesson and part personal reminiscences of his own activism, We All Want to Change the World will resonate with anyone who recognizes the need for social change and is willing to do the work to make it happen"--